English: English - Pertiwi, Putu Ratih; Sulistyawati, Agung Sri; Ratna Sari, Ni Putu (Faculty of Economics and Business, University of Mataram, 2025)
This study explores the everyday work practices of women who own and manage family-based homestays in Sayan Village, Ubud, Bali. The research aims to describe the operational roles undertaken by female owner-managers and examine how these responsibilities intersect with their domestic routines. A qualitative descriptive design was employed, involving in-depth interviews and non-participant observations with eight women who have operated their homestays for five to fifteen years. The findings indicate that women carry out a wide range of tasks, including housekeeping, breakfast preparation, guest relations, booking communication, and basic financial documentation. These responsibilities are performed alongside ongoing domestic duties, creating a continuous rhythm of household and tourism work within the same spatial and temporal setting. The study shows that women’s hands-on involvement forms the core of homestay service delivery and underpins the personalized atmosphere characteristic of family-run accommodations. These findings contribute to a deeper understanding of micro-level tourism labor in rural Bali and highlight the essential role of women in sustaining homestay quality.